Pemberdayaan Warga Golongan Menengah dalam Pembangunan di Perkotaan - H., Pauline R. (P2KK LIPI, 1998)
This article describes the role of the middle class people in the development of the cities. As Indonesia is facilitating its industrial sector, these middle class group plays an important role in absorbing the manpower and give life to millions of worker in the manufacturing sector as well as in other sectors. In the next decade the middle class group will be doubled in number and they become an agent of change and agent of development. These group will also become a bridge between the upper class and the lower class. The government must enhance, empower and stimulate these growing middle class in the urban areas as well as In the suburban areas. The suburbs will grow with lots of facilities like new statelite towns, in the BOTABEK (Bogor, Tanggerang and Bekasi) for Jakarta and other big cities. A study has been conducted in Surabaya especially on the settlements for these middle class group